2015
DOI: 10.1158/1078-0432.ccr-14-1324
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Choroid Plexus Tumors Reveals Novel Clinically Relevant Subgroups

Abstract: Purpose: To investigate molecular alterations in choroid plexus tumors (CPT) using a genome-wide high-throughput approach to identify diagnostic and prognostic signatures that will refine tumor stratification and guide therapeutic options.Experimental Design: One hundred CPTs were obtained from a multi-institutional tissue and clinical database. Copynumber (CN), DNA methylation, and gene expression signatures were assessed for 74, 36, and 40 samples, respectively. Molecular subgroups were correlated with clini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
115
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 88 publications
(126 citation statements)
references
References 20 publications
8
115
1
2
Order By: Relevance
“…Our series thus might help to explain the discrepancy between results obtained in previous pediatric series [1,4] as compared to older patient collectives [2]. The majority of aCPP occur in children younger than three years.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Our series thus might help to explain the discrepancy between results obtained in previous pediatric series [1,4] as compared to older patient collectives [2]. The majority of aCPP occur in children younger than three years.…”
mentioning
confidence: 77%
“…In the latter series, however, patients harboring atypical CPP were younger than in the first study [2], raising the possibility that increased mitotic activity might not have an adverse prognostic effect in younger children. Indeed, two recent studies suggested that CPP and aCPP in younger children show not only similar molecular profiles, but also comparable outcome [1,4]. These results are questioning the concept of aCPP, but might well be related to an age-dependent effect.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, the concurrent gain of TAF12, NFYC and RAD54L may serve to model an aberrant epigenome that promotes a proliferative, and relatively undifferentiated state ( TAF12 and NFYC ), while tolerating genotoxic stress ( RAD54L ). Interestingly, recent data indicate that CPCs that do not gain chromosome 1 retain both copies of this chromosome in an otherwise hypodiploid genome (Merino et al, 2014). Thus absolute or relative gain of this chromosome might be required for CPC development.…”
Section: Discussionmentioning
confidence: 99%
“…The radio-resistance of mCPC may reflect the Tp53 null status of these tumors, since this gene mediates cell death mechanisms in irradiated cells (39). Notably, 60% of human CPCs contain mutant Tp53 : these tumors also tend to be radio-resistant, clinically aggressive and to develop in infants (40, 41). It is interesting that our mCPC model is initiated in embryonic choroid plexus; therefore, these tumors likely model radio-resistant, aggressive and TP53 -mutant infant CPC (18).…”
Section: Discussionmentioning
confidence: 99%